Effect of Sustainable Infrastructure and Service Delivery on Sustainable Tourism: Application of Kruskal Wallis Test (Non-parametric) (http://dx.doi.org/10.31427/IJSTT.2022.5.2.1, 2022)
This study examined the effect of sustainable infrastructure and service delivery on sustainable tourism in Kashmir Valley through the five main destinations by covering essential stakeholders. At present, tourism potential nations face destination sustainability issues in various junctures of the tourism sector. Therefore, international agencies and nations focus on sustainable tourism through sustainable transport infrastructure, other factors and improved service delivery. Few studies underlined the role of sustainable infrastructure in service quality and their collective impact on sustainability without empirical evidence at the destination level. At this juncture, the current study presents the summaries of empirical investigation of the effect of sustainable transport infrastructure and services delivery on sustainable tourism in Kashmir Valley. For analysis, the Kruskal-Wallis test (non-parametric) is applied to assess the variation in sustainable tourism based upon the performance of sustainable infrastructure and service delivery at destinations. The application of the Kruskal-Wallis independent samples tests duly confirmed the significant results. Sustainable tourism differs by transport infrastructure performance, other elements and service quality of the destinations. Therefore, it is to be stated that poor functioning of transport infrastructure and other basic structures adversely affects service delivery and raises sustainability issues at destinations. It asserts that the comprehensive sustainable transport infrastructure, water supply and drainage, health and sanitation, solid and liquid waste management are highly required to combat environmental issues and ensure sustainability at destinations. The findings of the study have significant policy implications to promote green infrastructure, quality services and development of sustainable tourism at destinations.